Meningkatkan Kepuasan Nasabah Melalui Kualitas Pelayanan yang di Mediasi oleh Kepercayaan (Survey Pada BRI Kcp Unit Kuamang Kuning Kabupaten Bungo) - Andri Yandi (Universitas Batanghari, 2019)
This study aims to analyze the effect of service quality on customer trust and satisfaction, trust in customer satisfaction, and analyze the influence of service quality through trust as a variable intervening on customer satisfaction. the sample is 384. The method of collecting data uses a survey method, which is followed by a statistical method to test the hypothesis that is by path analysis. The results of this study indicate that service quality has a positive and significant effect on customer trust and satisfaction, as well as trust has a positive and significant influence on customer satisfaction. In addition, service quality through trust also has an influence on customer satisfaction.